Aspirations, Beliefs and a NewIdea: Building on March’s Other Model of Performance Feedback - Keil, Thomas; Posen, Hart E.; Workiewicz, Maciej (Academy of Management Review, 2023)
A central idea in the behavioral theory of the firm is that when an organization’s performance falls below aspirations, a search for solutions is triggered. While this aspiration-based model has dominated the empirical literature, it is only one of two Carnegie School accounts of how firms use performance feedback to regulate behavior. We call the second account the belief-based model. This model focuses on the characteristics of the choice alternatives faced by firms and the challenges inherent in evaluating them. Using a computational approach, we demonstrate that the predictions of the belief-based model may explain instances where search increases, rather than decreases, as performance improves. This behavioral pattern, both above and below the aspiration, is prevalent in empirical research but not well accounted for using the aspiration-based model alone. We then develop the integrated discovery and evaluation of alternatives (IDEA) model of problemistic search, which integrates the two models and identifies the organizational and environmental factors that induce one or the other constituent submodels. We highlight the implications for empirical research on performance feedback and extensions to account for additional theoretical constructs, such as affect and politics.